Evaluasi Aksesibilitas Learning Management System (LMS) Perguruan Tinggi Berdasarkan Standar WCAG 2.1 bagi Mahasiswa Disabilitas - Lukman Santoso; Agus Waryanto; Neilin Nikhlis; Dani Sasmoko (Universitas Harapan Bangsa, 2026)
This study evaluates the accessibility of 14 higher education Learning Management Systems (LMS) in Semarang City based on WCAG 2.1 standards using the WAVE tool to support SDG 4 (Quality Education). Employing a descriptive quantitative-evaluative approach on 28 public pages (homepages and login pages), the results revealed suboptimal and varying compliance. The platforms were categorized into three issue clusters: low (3 LMS), medium (7 LMS), and high (4 LMS). The most dominant violations occurred in the Perceivable principle (57.1%) due to contrast errors and the Understandable principle (35.7%) due to structural inconsistencies, with homepages generally exhibiting higher error rates than login pages. These findings confirm a functional digital divide for students with disabilities, necessitating a shift in campus IT governance toward a user-centered inclusive design.